Pengaruh Pengalaman Kerja dan Pelatihan Kerja Terhadap Kinerja Karyawan Engineering Maintenance PT XYZ - Iman; Aji Tuhagana; Zenita Apriani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Company's excellence center will be achieved with competent human resources towards the company's rapid competitiveness. This study aims to investigate how work experience and job training affect employee performance in the Engineering Maintenance Department Organisation at PT XYZ. Population and sample for this study included Engineering and Maintenance employees at PT XYZ. The research utilized multiple linear regression analysis as the primary method to examine the relationships between the variables. A quantitative approach was employed. Research sample was chosen using saturated sampling technique, the study involved a total of 35 respondents. Data analysis results indicate that work experience and job training significantly impact employee performance. According to the coefficient of determination test results, training and compensation contribute 43.2% to employee performance. From this research it is recommended to PT XYZ increase investment in training and develop strategies to enhance employee performance. This should help improve the quality standards of employee performance through training, enabling employees to gain more valuable experience, maintain a smooth production process, and produce high-quality goods.